Thoracoscopic resection of a type I pleuropulmonary blastoma: A case report - Maithah Mohammed Alkaabi; Najla Saleh Ben Ghashir; Tamer Hamed Ibrahim; Deepak Kishore Kaltari; Iftikhar Jan Suleman (Elsevier, 2023)
Background: Pleuropulmonary blastoma (PPB) is a rare form of sarcoma that originates in the pulmonary tissue. It has three anatomical types: I (mostly cystic), (solid and cystic), and III (mostly solid). We present a case of type I PPB presenting as a large cystic lung lesion managed thoracoscopically. Case presentation: A 5-month-old male with no prior medical history presented with symptoms resembling pneumonia. Blood work results were normal. Chest x-ray showed a large cyst occupying the lower part of the left hemithorax causing severe mediastinal shift. A computerized tomography (CT) with intravenous contrast was done and revealed a lesion suspicious for a congenital cystic pulmonary malformation (CPAM). No systemic arterial vessels were going to the cystic lesion. A thoracoscopy was done using one-lung ventilation. Complete resection of the cystic mass was accomplished thoracoscopically using a coagulation device and endo-staplers. A chest tube was left in place. The patient had an uneventful recovery and was discharged home in a stable condition. The pathology analysis confirmed a completely resected type I PPB. At four months of follow-up there have been no signs of recurrence. Conclusion: PPB must be included in the differential diagnosis of children with cystic lung lesions. Complete thoracoscopic excision is possible.